Essence of Internet Marketing strategies - T. D. Kolodnik (Цифровая трансформация)
As a result of the analysis of scientific literature, different views on the explanation of Internet marketing strategies are noticed. The author believed that understanding the goals of these strategies would allow to comprehend their essence and understand the methods mastered on the application of complex technologies and services of the Internet. It has been substantiated that the use of these technologies and services in marketing activities enhances the competitiveness of companies.